Influence of solid-state electrolyte on 2D SnS2 field effect transistors. (29th May 2019) - Lv, Wenxing; Wang, Bochong; Lv, Weiming; Cao, Shiwei; Luo, Xin; Shi, Wenhua; Zhang, Baoshun; Wei, Zhongming; Zeng, Zhongming
Abstract: Transition metal-dichalcogenides (TMDs) have attracted considerable interests due to their unique combination of gate-tunable charge carriers, high mobility, and sizable band gap. Here, we report the effect of solid-state ionic liquid top-gate on SnS2 field effect transistors (FETs). The transport measurements indicate that the threshold voltage V th in transport curves shifts significantly in the positive V tg direction. By utilizing a hybrid solid-state ionic liquid/solid electric dual-gate geometry acting on the SnS2 channel, an enhancement of carrier mobility is observed due to the reduction of barrier height by band bending and the increase of carrier concentration. Our study provides a framework for understanding the effect of different dielectrics on SnS2 FETs and paves the way for further exploration of their prospects for electronic and optoelectronic devices.